Comparative Analysis of Semantic and Morphosyntactic Peculiarities of the Demonstratives in the Eastern Khanty and the Southern-Central Selkup Languages; Mediterranean Journal of Social Sciences; Vol. 6, № 2 S1 - Vorobyeva V. V. Viktoriya Vladimirovna (2015, 2015)
Title screen